Current and future use of point-of-care tests in primary care: an international survey in Australia, Belgium, The Netherlands, the UK and the USA - Howick, J; Cals, J; Jones, C; Price, C; Plüddemann, A; Heneghan, C; Berger, M; Buntinx, F; Hickner, J; Pace, W; Badrick, T; Van Den Bruel, A; et al. (BMJ Publishing Group, 2014)
OBJECTIVE: Despite the growing number of point-of-care (POC) tests available, little research has assessed primary care clinician need for such tests. We therefore aimed to determine which POC tests they actually use or would like to use (if not currently available in their practice). DESIGN: Cross-sectional survey. SETTING: Primary care in Australia, Belgium (Flanders region only), the Netherlands, the UK and the USA. PARTICIPANTS: Primary care doctors (general practitioners, family physicians). MAIN MEASURES: We asked respondents to (1) identify conditions for which a POC test could help inform diagnosis, (2) from a list of tests provided: evaluate which POC tests they currently use (and how frequently) and (3) determine which tests (from that same list) they would like to use in the future (and how frequently). RESULTS: 2770 primary care clinicians across five countries responded. Respondents in all countries wanted POC tests to help them diagnose acute conditions (infections, acute cardiac disease, pulmonary embolism/deep vein thrombosis), and some chronic conditions (diabetes, anaemia). Based on the list of POC tests provided, the most common tests currently used were: urine pregnancy, urine leucocytes or nitrite and blood glucose. The most commonly reported tests respondents expressed a wish to use in the future were: D-dimer, troponin and chlamydia. The UK and the USA reported a higher actual and desired use for POC tests than Australia, Belgium and the Netherlands. Our limited data suggest (but do not confirm) representativeness. CONCLUSIONS: Primary care clinicians in all five countries expressed a desire for POC tests to help them diagnose a range of acute and chronic conditions. Rates of current reported use and desired future use were generally high for a small selection of POC tests, but varied across countries. Future research is warranted to explore how specific POC tests might improve primary care.